PENGARUH PENDEKATAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN SPASIAL SISWA PADA MATERI BANGUN DATAR DI KELAS IV SD NEGERI 101770 TEMBUNG - Riski Nadeak; Nur Hudayah; Elvi Mailani; Syahrial; Suyit Ratno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of the Realistic Mathematics Approach on students’ spatial abilities in the topic of plane figures in the fourth grade at SD Negeri 101770 Tembung during the 2025/2026 school year. This study employed a quasi-experimental method using a Nonequivalent Control Group Design. The study subjects consisted of 41 students, including 23 students in the experimental class and 18 students in the control class. The research instrument was a multiple-choice spatial ability test that met the criteria for validity, reliability, difficulty level, and discriminative power. Data analysis was conducted using Normalized Gain (N-Gain) scores, which were subsequently tested for normality, homogeneity, and analyzed using an Independent Samples t-test with the assistance of SPSS version 26. The results showed that the average N-Gain for the experimental class was 0.7877, which falls into the high category, while the average N-Gain for the control class was 0.5333, which falls into the moderate category. The results of the hypothesis test showed a significance value (Sig., 2-tailed) of 0.000 (< 0.05), indicating a significant difference in the improvement of spatial ability between the two classes. These findings suggest that the Realistic Mathematics Education approach is more effective than the Teacher-Centered Learning approach in improving students’ spatial ability. This effectiveness is supported by the characteristics of the Realistic Mathematics Education approach, which utilizes real-world contexts, exploratory activities, discussions, and the process of knowledge construction, enabling students to build visual representations, understand relationships between shapes, and develop their visualization, relational, and spatial orientation skills in a more meaningful way when studying plane figures.